The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/2333721418768998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrical Stimulation on Skeletal Muscle of Old Sedentary People

Abstract: Physical activity plays an important role in preventing muscle atrophy and chronic diseases in adults and in the elderly. Calcium (Ca2+) cycling and activation of specific molecular pathways are essential in contraction-induced muscle adaptation. This study attains human muscle sections and total homogenates prepared from biopsies obtained before (control) and after 9 weeks of training by electrical stimulation (ES) on a group of volunteers. The aim of the study was to investigate about the molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Interestingly this was accompanied with the upregulation of Calsequestrin-1. In a recent study on humans, it was shown that these changes were reversed after 9 weeks of training by electrical stimulation [63] of the vastus lateralis muscle of sedentary senior volunteers. The decreased active SERCA, and thus insufficient SR Ca 2+ content, can also be explained by the findings of Boncompagni et al [64].…”
Section: Oxidative Stress and Ec-coupling Machinery In Agingmentioning
confidence: 99%
“…Interestingly this was accompanied with the upregulation of Calsequestrin-1. In a recent study on humans, it was shown that these changes were reversed after 9 weeks of training by electrical stimulation [63] of the vastus lateralis muscle of sedentary senior volunteers. The decreased active SERCA, and thus insufficient SR Ca 2+ content, can also be explained by the findings of Boncompagni et al [64].…”
Section: Oxidative Stress and Ec-coupling Machinery In Agingmentioning
confidence: 99%
“…The conclusions were that neuromuscular ES applied to Vastus lateralis muscle of sedentary seniors combines fiber remodeling with activation of Ca 2+ -Calmodulin molecular pathways and modulation of the key Ca 2+ -handling proteins. 80 Collagen expression was also reported to be remodelled during both volitional physical exercise and ES; indeed, expression of three different forms of collagen was upregulated in electrically stimulated muscle. 30 However, the increase in collagen expression seems not to stimulate fibrosis as is shown by both morphological evidence and at the level of important fibrosis modulators, namely the increase in expression of miR29.…”
Section: Role Of Myokines In Volitional Physical Activity and Hbfes Tmentioning
confidence: 99%
“…30 In addition, with ES an increase in expression of IGF-1 factors as well as markers of both satellite cell proliferation and extracellular matrix remodeling was detected along with downregulation in the expression of proteases just as occurs during volitional physical exercise. 31 Furthermore, Mosole et al, 80 recently demonstrated that ES modulate also the Calcium (Ca 2+) -handling proteins, NFAT, and related proteases. The aims were to study the molecular mechanisms that support functional muscle improvement by ES.…”
Section: Role Of Myokines In Volitional Physical Activity and Hbfes Tmentioning
confidence: 99%
“…ES treatment in old sedentary people improved muscle performance, increasing fiber size, stimulating satellite cells and modulating the degeneration of the mitochondrial apparatus [106,107]. Moreover, it has been reported that ES treatment increases the number of fast twitch fibers [108] and counteracts neuromuscular disabilities from age related NMJ degeneration in paraplegic patients [109,110]. At molecular level ES treatment activates signaling pathways that decode for a specific calcium signaling involved in metabolic and structural adaptation of muscle fibers, such as the Calcineurin-NFAT and CamKII pathways that control the maintenance or switching of muscle fiber type [108].…”
Section: Als and Aging As Paradigmatic Examples Of Altered Nerve-mmentioning
confidence: 99%
“…Moreover, it has been reported that ES treatment increases the number of fast twitch fibers [108] and counteracts neuromuscular disabilities from age related NMJ degeneration in paraplegic patients [109,110]. At molecular level ES treatment activates signaling pathways that decode for a specific calcium signaling involved in metabolic and structural adaptation of muscle fibers, such as the Calcineurin-NFAT and CamKII pathways that control the maintenance or switching of muscle fiber type [108]. Moreover, it has been described that biphasic electrical stimulation significantly increases the number and size of AChRs clusters available for NMJ formation during innervation [105] and that electrical stimulation promotes axonal growth and sensorimotor functional recovery after injury [106].…”
Section: Als and Aging As Paradigmatic Examples Of Altered Nerve-mmentioning
confidence: 99%